2019
DOI: 10.3389/fpsyg.2019.00182
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-Historical Contextualization for Music and Visual Works: A Literature Review and Comparison Between Artistic Mediums

Abstract: A significant contribution to the literature on aesthetics in the last decade has been Bullot and Reber's ecologically-driven psycho-historical framework for the science of art appreciation (PHF). The framework proposes that the presence of contextualizing information accompanying an artwork will impart a substantial impact on appreciation for it, which is accessible through understanding of the causal information surrounding the work. Artistic understanding is out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 44 publications
1
20
2
Order By: Relevance
“…This paper reported the results of a literature review on the impact of valenced framing on music preference (study 1) and two subsequent empirical studies on music preference for participants receiving one of three types of framing/enrichment (study 2 and study 3). In contrast to the findings of an existing literature review on the impact of historical framing (Chmiel and Schubert, 2019a), study 1 concluded that positively valenced framing had a significant, positive impact on preference 50% of the time. Additionally, study 1 further confirmed previous observations that existing studies on framing have almost exclusively contained typical music stimuli such as popular music and accessible forms of classical and jazz music.…”
Section: General Discussion and Conclusioncontrasting
confidence: 82%
See 3 more Smart Citations
“…This paper reported the results of a literature review on the impact of valenced framing on music preference (study 1) and two subsequent empirical studies on music preference for participants receiving one of three types of framing/enrichment (study 2 and study 3). In contrast to the findings of an existing literature review on the impact of historical framing (Chmiel and Schubert, 2019a), study 1 concluded that positively valenced framing had a significant, positive impact on preference 50% of the time. Additionally, study 1 further confirmed previous observations that existing studies on framing have almost exclusively contained typical music stimuli such as popular music and accessible forms of classical and jazz music.…”
Section: General Discussion and Conclusioncontrasting
confidence: 82%
“…However, no studies as yet have directly compared these types of framing within the same experimental design. An additional finding reported by Chmiel and Schubert (2019a) was a discrepancy in the type of stimuli used between the two examined mediums (music works and visual works). The music stimuli used in the existing literature were almost exclusively of a "typical" nature, such as popular music and accessible forms of classical music and jazz (that is, not including styles such as atonal music or experimental/free jazz).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Meanwhile, a separate line of empirical research that is potentially relevant here involves the assessment of people's sensitivity to so-called cross-media artistic styles (see Hasenfus et al, 1983; see also Chmiel and Schubert, 2019;Lessing, 1766Lessing, /1962; though see Wellek and Warren, 1948). So, for example, Hasenfus et al presented aesthetically naïve observers with a range of reproductions of unfamiliar paintings, examples of architecture, poetry, and music (15 in each category) from several different historical epochs/styles.…”
Section: Music-painting Correspondencesmentioning
confidence: 99%